The Influence of Financial Behavior on Financial Well-Being Through Financial Satisfaction - Ida Subaida (Jurnal Ekonomi Pembangunan, 2024)
Good financial behavior will encourage the creation of financial satisfaction and can be a factor that will increase financial well-being. Financial satisfaction can include one's life satisfaction with financial amounts. Financial well-being is the possession of sufficient resources for a comfortable life. This study aims to examine financial behavior that influences financial well-being, both directly and indirectly. The selected population is stock investors. Investors are selected using quota sampling. The data analysis used is path analysis. The results of the study report that financial behavior has a significant effect on financial satisfaction and well-being, but financial behavior does not affect financial well-being. Financial satisfaction mediates the impact of Financial behavior on Financial well-being.